Radicular dysfunction preponderance at early phase clinical evaluation in myelitis by Schistosoma mansoni - Claudio Henrique Fernandes Vidal; Joacil Carlos da Silva; Jefferson Jane Oliveira Souza; Sara Pimentel Belleza Bernardino; Maria Lucia Brito Ferreira (Arquivos de Neuro-Psiquiatria)
In neuroschistosomiasis, the spinal cord is the most common place of the disease. In high prevalent areas for schistosomiasis mansoni, the clinical alertness is important for an early diagnostic, in order to decrease the final neurological damage. This study provides some useful neurologic information about a series of patients with schistosomal myelitis. METHOD: The sample consisted of 13 schistosomiasis mansoni carriers examined at the moment of the diagnosis of myelitis. RESULTS: The classical triad (lumbago, weakness at the lower limbs and urinary dysfunctions) was documented in 11 (86.61%) patients. The distribution of the clinical forms was: myeloradicular in six patients (46.15%), radicular in four (30.76%) and myelitic in three (23.07%). CONCLUSION: The radicular dysfunction and their clinical associated forms were the most prominent pattern during the early phase of this disease.